ASURANSI BPJS TINJAUAN PELEPASAN INFORMASI REKAM MEDIS UNTUK KLAIM ASURANSI BPJS KESEHATAN DI RSUD KANJURUHAN KEPANJEN - Miftachul Ulum (JRMIK, 2023)
Payment is a very important activity in a hospital. One way of payment of health care in hospital is BPJS of health. Issues contained in the release of medical record information for insurance claims BPJS of health in Kanjuruhan Kepanjen Hospital is not yet completed the requirements of the claims, especially the summary sheet and the sheet out the verification and dissemination SOP has been no release of medical record information for insurance claims BPJS of health. The research method in this study using descriptive research method. The results showed that participants BPJS of health insurance in the first quarter 2019 in Kanjuruhan Kepanjen Hospital is the highest number of patients with a percentage of 61% of the 3,553 inpatients. Problems that hinder the process of insurance claims is not yet complete BPJS claim requirements, especially the summary sheet out and verification with a percentage of 28.12% in January, 36.26% in February and 36.08% in March, another problem is the lack of socialization to the SOP involved in the release of medical record information primarily to the medical staff who are in the inpatient unit. Keywords: Insurance, BPJS of health, Release, Medical Record